Cold sintering of BaZr0.7Ce0.2Y0.1O3-δ ceramics by controlling the phase composition of the starting powders. (February 2023) - Kindelmann, Moritz; Ebert, Julian Norbert; Scheld, Walter Sebastian; Deibert, Wendelin; Meulenberg, Wilhelm Albert; Rheinheimer, Wolfgang; Bram, Martin; Mayer, Joachim; Guillon, Olivier
Abstract: Protonic ceramic conductors based on the solid solution BaZr0.7 Ce0.2 Y0.1 O3-δ (BZCY72) have great potential as electrolytes in various energy conversion devices. However, their refractory nature requires very high sintering temperatures to achieve sufficient densification for gas tightness. In this study, we present a novel processing route using the cold sintering process (CSP) to consolidate BZCY72 powders at 350°C using 400 MPa and deionized water as a sintering aid. Through a systematic variation of the calcination pretreatment, we demonstrated that the cold sintering ability of BZCY can be tuned through the phase composition of the starting powder. The cold sintering process of BZCY bases on a decomposition reaction of a Ce-rich BZCY phase, which plays a major role for low temperature densification. A subsequent post thermal treatment (PTT) at 1300°C is sufficient to regain the BZCY phase resulting in total conductivities of 1*10 −3 Scm −1 at 500°C in air. Graphical abstract: Image, graphical abstract